The Bella Coola Valley : Harlan I. Smith's fieldwork photographs, 1920-1924 - Tepper, Leslie Heyman, 1947- (Mercury series., 1991)
This catalogue presents sites, activities and portraits recorded by Harlan I. Smith while doing ethnographic fieldwork among Nuxalk, Chilcotin and Carrier people in the Bella Coola valley, British Columbia between 1920 and 1924.